Tuning the Elasticity of Nanogels Improves Their Circulation Time by Evading Immune Cells. (7th April 2022) - Desai, Prachi; Rimal, Rahul; Florea, Alexandru; Gumerov, Rustam A.; Santi, Marta; Sorokina, Anastasia S.; Sahnoun, Sabri E. M.; Fischer, Thorsten; Mottaghy, Felix M.; Morgenroth, Agnieszka; Mourran, Ahmed; Potemkin, Igor I.; et al.
Abstract: Peptide receptor radionuclide therapy is used to treat solid tumors by locally delivering radiation. However, due to nephro‐ and hepato‐toxicity, it is limited by its dosage. To amplify radiation damage to tumor cells, radiolabeled nanogels can be used. We show that by tuning the mechanical properties of nanogels significant enhancement in circulation half‐life of the gel could be achieved. We demonstrate why and how small changes in the mechanical properties of the nanogels influence its cellular fate. Nanogels with a storage modulus of 37 kPa were minimally phagocytosed by monocytes and macrophages compared to nanogels with 93 kPa modulus. Using PET/CT a significant difference in the blood circulation time of the nanogels was shown. Computer simulations affirmed the results and predicted the mechanism of cellular uptake of the nanogels. Altogether, this work emphasizes the important role of elasticity even for particles that are inherently soft such as nano‐ or microgels. Abstract : Small changes in the elasticity of the inherently soft radiolabeled nanogels show major differences in its in vivo circulation half‐life. Longer circulation life renders a higher possibility for nanogels to accumulate in the tumor microenvironment by enhanced permeation and retention effect.